Policy and politics in disjuncture in an age of secular stagnation - Ansell, B; Gingrich, J (Cambridge University Press, 2022)
Across advanced industrial democracies, the financial crisis of 2008 ushered in not just deep economic adjustments but political ones. In many countries, dominant political parties lost voters while new populist parties gained them. Political economists responded to these shifts by asking how the crisis had changed – or failed to change – both what citizens want and politicians’ ability to respond to these wants. But what if the political responses to the crisis reflect not an idiosyncratic shock but instead a much longer term systematic slowdown of advanced economies that has more permanently reshaped the scope for political responsiveness?